Organic growth disciplines : a strategic framework for imagining business growth opportunities - Sudharshan, Devanathan (Emerald Publishing Limited, 2019)
If your firm doesn't grow sustainably, can you grow professionally?Growth should be an integral part of every company, and organic internal growth must be carefully managed in order to foster successful and sustainable growth. In Organic Growth Disciplines, business expert Devanathan Sudharshan introduces a new framework for exploring the fuzzy front end of the search for growth opportunities.Bringing together six organic growth disciplines, this new approach arms readers with a language to use in professional discussions on the growth-based future of their firms.The disciplines detailed are rooted in explorations of opportunities involving knowledge, technology, needs, customers, pricing, leveraging, and acceleration. Looking at examples from businesses and industries at the forefront of today's society, including Google, Apple and Amazon, and Zappos, this book not only looks at what organic growth disciplines are, but also how to implement them in your company. Written for both practitioners and students, this fresh look at growing organically provokes its readers to imagine new horizons. It is an invaluable addition to existing books on new product, technology, and strategic management.